Advances in the use of microvascular flaps for postoperative defect repair in complex abdominal surgery: innovative approaches to recovery and functionality - Bustos, Jorge A. R.; Jativa, Miguel A. G.; Salazar, Eduardo R. A.; Ayala, Rony M.; Mora, Diana P. A.; Venegas, Dilan K. A.; Perdomo, Santiago P. (International Journal of Research in Medical Sciences, 2024)
Flap reconstruction technique was introduced by Sir Harold Gillies during WWI which is now evolved into microsurgical advancements in the 1970s enabling precise tissue transfer for complex reconstructions. By the 1980s, microvascular flaps matured period, offering durable solutions for extensive abdominal defects especially after oncological resections, infections, or previous surgeries. Our systematic strategy of papers selection focused on microvascular flap techniques in abdominal wall reconstruction. Studies that disuses latest advancements are extracted from papers published from 2020-2024. Proper inclusion and exclusion criteria is followed, papers are selected from peer-reviewed Journals, clinical trials, systematic reviews and meta-analysis and reviews. Results show that advancements in microvascular flap surgery have improved postoperative abdominal defect repairs. Innovations include precise microvascular techniques, perforator and free flaps, composite and propeller flaps, and the gracilis free muscle flap. Enhanced preoperative imaging, such as magnetic resonance angiography (MRA) and computed tomography angiography (CTA) and improved flap engineering techniques lead us to superior outcomes with less complications. Recent innovations in microvascular flap techniques have innovated abdominal defect reconstruction and suppressed traditional techniques. These advancements are offering enhanced precision, functionality, and aesthetic results. Advanced imaging and novel flap engineering methods along with technological advancements has optimized surgical outcomes.